TAX CONTROL: PROBLEMS AND SOLUTIONS - Mamajonov Lazizbek , Azamjonovich (THE INNOVATION ECONOMY, 2025)
The article examines the necessity and importance of tax control. It also analyzes cases of violations of tax legislation by business entities and makes proposals for their prevention.